Supplementation of multi-enzymes alone or combined with inactivated Lactobacillus benefits growth performance and gut microbiota in broilers fed wheat diets - Gao, Qingtao; Wang, Yanchun; Li, Jiaheng; Bai, Guosong; Liu, Lei; Zhong, Ruqing; Ma, Teng; Pan, Hongbin; Zhang, Hongfu (Frontiers in Microbiology, 2022)
The effects of multi-enzymes mixture supplementation or combined with inactivated Lactobacillus on growth performance, intestinal barrier, and cecal microbiota were investigated in broilers at the age of 15 to 42 days fed wheat-based diet. A total of 576 chicks (12 birds/cage; n = 12) were used and divided into four groups, and randomly allotted to 4 experimental diets throughout grower (15 to 28 d of age), and finisher (29 to 42 d of age) phases. Diets consisted of a corn-soybean meal-based diet (BD), a wheat-soybean meal-based diet (WD), and WD supplemented multi-enzymes (WED) or combined with inactivated Lactobacillus (WEPD). The results showed that the average daily gain (ADG) and body weight (BW) were reduced in broilers fed WD diet compared with those fed BD diet during grower period (P < 0.05). Broilers in WED or WEPD group had higher ADG and BW during the grower period (P < 0.05) and had lower feed-to-gain ratio (F/G) compared to broilers in WD group during the grower and overall periods (P < 0.05). Improved expression of intestinal barrier genes (claudin-1, ZO-1, and mucin-2) were observed in birds fed WEPD diet compared to those received BD or WD group (P < 0.05). There were 5 bacterial genera decreased in WD group when compared to BD group (P < 0.05). Among which, Flavonifractor and Sellimonas were tended to improve in WED group, and Sellimonas was improved in WEPD group (P < 0.05) compared with those in WD group. Additionally, chickens fed WED and WEPD diets improved unclassified_f_Lachnospiraceae and Eubacterium_hallii_group compared to those fed WD or BD group (P < 0.05). Higher acetate and total SCFA concentrations were observed (P < 0.05) among birds received WD diet. Broilers fed WED or WEPD diet further improved cecal propionate (P < 0.05) and tended to improve butyrate concentration when compared with WD diet. These results suggested that supplemental multi-enzymes alone and combined with inactivated Lactobacillus could improve the reduced growth performance of broilers fed wheat-based diet, and inactivated Lactobacillus had additional protective effect on intestinal barrier function of broilers.